The COVID-19 pandemic and the use of urban public parks in Garanhuns – PE (Research, Society and Development, 2021)
The objective of the research was to identify the current situation of the use and function of parks during the COVID-19 pandemic period through the use of a behavioral map centered on places, in two urban parks in Garanhuns – PE. Knowing that the behavioral map is important for understanding the relationship between the environment and the behavior of free areas, as they provide a picture of the different types of behavior and their frequencies, observations were carried out in the morning and afternoon, in order to compare the use of space in these two periods. From the pre-established route, observation points were created, which resulted in behavioral maps of the activities that were taking place in the environment and the type of user found at the time of observation. From the analysis carried out in the parks under study, it was possible to identify 06 categories of users, which are related to the age group and activity performed at the site, it was noticed that the parks have different functions, public and activities, due to the equipment present. inside, it was also detected that there is a lack of care with one of the parks, since the lack of maintenance in some equipment was identified.